Antidiabetic Activity Of Barley Porridge On Postprandial Blood Glucose And Histopathology Of Alloxan-Induced Diabetics Rats - Celin Celin; Meldawati Meldawati; Yeni Halim (Eduvest - Journal of Universal Studies, 2024)
Diabetes mellitus (DM) is a critical global health issue, characterized by high morbidity and mortality rates associated with various complications. In Indonesia, the incidence is projected to reach 28.6 million by 2045, positioning the country among the highest globally. The aim of this study is to evaluate the effects of barley as a food ingredient on blood sugar levels and pancreatic histopathology. The study involved dividing the mice into six groups, with six mice in each group. These groups were: normal control (K), negative control (KN) induced with alloxan 125 mg/kg BW intraperitoneally, positive control (KP) with oral metformin 9 mg/200 g BW, normal barley rats (P1), DM barley rats (P2), and DM rats with mixed food (P3). Phytochemical screening was also conducted on barley porridge to identify the presence of flavonoids, glycosides, alkaloids, and saponins. The KP and P2 groups were more effective in reducing blood sugar levels than the KN and P3 groups. In the Kruskal-Wallis test, there was no significant difference between groups P2 and KP on postprandial blood sugar levels, indicating that barley produced an effect similar to metformin (p-value = 0.0395). Pancreatic histopathology observations showed that groups P2, P3, and KP had the same damage score of 2. Barley demonstrated a comparable antidiabetic effect to metformin, as evidenced by similar results in blood sugar reduction and pancreatic histopathology scores in the P2 and KP groups